Immune activation‐ and regulation‐related patterns in stable hand transplant recipients. (8th December 2016) - Kamińska, Dorota; Kościelska‐Kasprzak, Katarzyna; Krajewska, Magdalena; Chełmoński, Adam; Jabłecki, Jerzy; Żabińska, Marcelina; Myszka, Marta; Banasik, Mirosław; Boratyńska, Maria; Gomółkiewicz, Agnieszka; Dzięgiel, Piotr; Klinger, Marian
Summary: We assessed cell subsets and expression of a set of genes related to the T‐cell populations in peripheral blood mononuclear cells to elucidate whether immune status of stable hand transplant recipients (HTx) differs from stable kidney transplant recipients (KTx). The study was conducted on five HTx 4.8 ± 1.7 years after transplantation and 30 stable KTx 7.9 ± 2.4 years after transplantation as well as 18 healthy volunteers. The research involved PBMC gene expression analysis of CD4, CD8, CTLA4, GZMB, FOXP3, IL10, IL4, ILR2A, NOTCH, PDCD1, PRF1, TGF‐B, and TNF‐A genes on a custom‐designed low‐density array (TaqMan) as well as flow cytometry assessment of lymphocyte subpopulations. HTx presented significantly increased expression of immunomodulatory genes ( TNF, IL10, GITR, and PDCD1 ) compared to KTx and controls. HTx revealed a proinflammatory molecular pattern with higher expression of NOTCH and CD8 compared to KTx and controls. KTx showed a reduced level of regulatory T cells compared to controls and HTx. Both HTx and KTx presented an increased number of CD8 + and CD8 + CD28 − T cells compared to controls. Stable hand transplant recipients exhibit persistent immune activation with rejection‐related gene expression pattern counterbalanced by secondary induction of regulatory mechanisms.